2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2015
DOI: 10.1109/embc.2015.7319904
|View full text |Cite
|
Sign up to set email alerts
|

Locomotion and eye behaviour under controlled environment in individuals with Alzheimer's disease

Abstract: This study aimed to examine simple locomotion and eye behaviour of individuals with Posterior Cortical Atrophy (PCA) and typical Alzheimer's disease (tAD) within a simulated real-world environment. Posterior cortical atrophy (PCA) is a neurodegenerative condition characterised by parietal, occipital and occipito-temporal tissue loss and progressive impairment of higher-order visual function in contrast to relatively spared memory and language. Targeted types of locomotion were walking in a series of corridors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…More advanced AD was associated with orientation to lower visual space. Similarly, Suzuki et al [ 83 ] found that the durations of fixations across all of the locomotion tasks (e.g., walking through corridors, walking up or down stairs, walking through a room with or without an obstacle) did not significantly differ between the AD patient and HOC.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…More advanced AD was associated with orientation to lower visual space. Similarly, Suzuki et al [ 83 ] found that the durations of fixations across all of the locomotion tasks (e.g., walking through corridors, walking up or down stairs, walking through a room with or without an obstacle) did not significantly differ between the AD patient and HOC.…”
Section: Resultsmentioning
confidence: 93%
“…Five [ 25 , 46 , 51 , 64 , 83 ] of the studies included here analysed eye movements during real-life simulations. Specifically, two of such studies analysed eye movement behaviours during every-day tasks [ 25 , 51 ], and the remaining two employed tasks that simulated real-life situations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the PwAD showed a lower proportion of relevant fixations compared to control subjects. In the work by Suzuki et al [ 28 ] eye movement is investigated during locomotion. One AD patient, one Posterior Cortical Atrophy (PCA) patient, and one healthy subject used an eye tracking device while performing locomotion activities (walking along corridors, up and down stairs, and across a room with or without obstacles).…”
Section: Eye Movements and Alzheimer's Diseasementioning
confidence: 99%